2014
DOI: 10.4028/www.scientific.net/amr.887-888.49
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Properties of Polybenzoxazine/TiC Hybrids

Abstract: In this work, typical polybenzoxazine, as new class of phenolic resin, has been used as a matrix for preparing a series of high performance hybrid materials using various amounts of titanium carbide (TiC) ranging between 0-10 wt% as fillers, via a solution blending technique. The thermal properties of bisphenol A-aniline base benzoxazine monomers (BA-a) and TiC mixtures have been studied by differential scanning calorimetry (DSC). The thermal stability of their cured hybrids has been tested by means of thermog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…These results also show that the addition of HGMS can also reduce the fire hazard, similar results were observed by Jiao and coworkers during their studies with polyurethane 11 . Similar results are already reported for several inorganic fillers‐based polybenzoxazine composites, as aluminum nitride, 43 silicon nitride, 27 and titanium carbide 44 …”
Section: Resultssupporting
confidence: 89%
“…These results also show that the addition of HGMS can also reduce the fire hazard, similar results were observed by Jiao and coworkers during their studies with polyurethane 11 . Similar results are already reported for several inorganic fillers‐based polybenzoxazine composites, as aluminum nitride, 43 silicon nitride, 27 and titanium carbide 44 …”
Section: Resultssupporting
confidence: 89%
“…4, the presence of more SiC particles involves a decrease in the heat polymerization (DH) of the composites. In fact, this energy decreased by 33.6% when the micro-SiC content increased from 0 to 20 wt.%, thus it is clear that the incorporation of the microfillers does not catalyze or enhance the polymerization of the phthalonitrile monomers; this is due to a well-known effect attributed to the ceramics which increases the viscosity of the thermoset materials resulting in an enhancement of the curing temperature [41].…”
Section: Dsc Analysismentioning
confidence: 97%
“…Devaraju and Sivasamy [ 107 ] also studied the influence of zinc oxide (ZnO) nanofillers in sisal fiber laminate and observed that the addition of 0.5 wt% of nanofiller improved the mechanical properties than the neat polymer and sisal‐based polymer composites. Ramdani et al [ 108 ] produced polybenzoxazine nanocomposites by incorporating the required amount of treated nano‐Si 3 N 4 varied from 5 and 30 wt% with an increment of 5 wt% in a cylindrical glass container. The addition of silicon nitride particles significantly enhanced the elastic modulus and tensile strength for the polybenzoxazine.…”
Section: Mechanical Propertiesmentioning
confidence: 99%